Use of light emitting diodes (LEDs) are effective and useful for sand fly ecoepidemiology studies in an Amazonian environment - Silva, Michelli Santos da (2022)
This study was partly financed by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior - Brasil (CAPES) - Financial code 001, and to FAPERO - Chamada 012/2016 – Diversidade Genética de Flebotomíneos no Estado de Rondônia e Avaliação dos Ciclos de Transmissão de Leishmanioses. The authors would also like to thank the Program for Technological Development in Tools for Health-PDTIS/FIOCRUZ for the use of its facilities.